Bandgap‐Opened Bilayer Graphene Approached by Asymmetrical Intercalation of Trilayer Graphene. Issue 9 (2nd December 2014) - Zhan, Da; Yan, Jia Xu; Ni, Zhen Hua; Sun, Li; Lai, Lin Fei; Liu, Lei; Liu, Xiang Yang; Shen, Ze Xiang
Abstract : A novel graphene structure formed by asymmetrical intercalation of FeCl3 molecules into a trilayer graphene is reported. The trilayer graphene is divided into a single layer and a bilayer graphene by the inserted FeCl3 layer. Theoretical calculation shows that such graphene bilayers with broken inversion symmetry present a prominent opened bandgap of ∼0.13 eV.